THE EFFECT OF PILATES EXERCISE THERAPY ON PAIN DISMINORE IN ADOLESCENT WOMEN IN THE SABILUL HASAN POINT ZAINUL HASAN GENGGONG PROBOLINGGO - Ulfa Nurul Afifah; Nur Hamim; Shinta Wahyusari (Media Inovasi Pendidikan dan Publikasi, 2023)
Dysmenorrhea is a marker of scarring (inflammation) in the human endometrium that occurs during endometrial and menstrual periods. The purpose of this study was to determine the effect of pilates exercise on dysmenorrhea pain in young women at Pondok Putri Sabilul Hasan. This research method used a pre-experimental design with a one grub pre-post test design. Total population of 28 respondents with total sampling technique. The results of the study were obtained from the results of the statistical test pvalue = 0.000. this shows that pilates exercise affects minorore pain which decreases pain during menstruation as seen from the results of the statistical value test 0.00 <0.003. It can be concluded that pilates exercise can reduce dysmenorrhea pain so that in future research it is expected to be able to examine other factors that affect dysmenorrhea and increase the number of samples, so that research results can be maximized.